Efectos del salario básico unificado sobre el empleo en la región sierra del Ecuador período 2010-2016 - Buñay Pilamunga, Verónica Elizabeth (2017)
It was developed with the purpose of analyzing the effects of unified basic salary on employment in the sierra region of Ecuador in the last seven years; in which there have been significant increases in wages, which have reached a greater purchasing power that even cover the basic family basket. Numeral 1 and its sections are made up of: The Problem Approach, which describes the importance of knowing the effects of basic salary on employment and how it affects employment for decision making. In addition, it includes Justification and Objectives. Numeral 2 and its sections are made up of: The Theoretical Foundation on wages, employment, wage setting mechanisms and employment policies. Numeral 3 and its respective sections is conformed by: The Applied Methodology in the research, the Population and Sample, Techniques, econometric methodology that corresponds to the investigation. Numeral 4 and its respective sections are conformed by, Analysis and Discussion of Results, application of the econometric model Numeral 5 and its respective sections are conformed by: The Conclusions and Recommendations of the research."